2015
DOI: 10.1627/jpi.58.245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Leaf-derived Surfactants on Wettability Alteration and Interfacial Tension Reduction in Water-oil System: EOR Application

Abstract: In this study, two types of plants based natural cationic surfactants, named Mulberry and Henna are introduced and the application of these natural surfactants in wettability alteration of reservoir rock and reducing the interfacial tension of water-oil system is investigated. For this purpose, two natural-based surfactants were extracted from the leaves of the trees of addressed plants and then the interfacial tension (IFT) values between oil and natural surfactant solution and also the contact angle values b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
(4 reference statements)
1
14
0
Order By: Relevance
“…DI water showed a contact value of 70° after 8 min. A similar study was reported in the literature where reduction in the contact angle from 62.5° to 48.5° was observed for mulberry leaf extract and 66° to 37° for Henna leaf extract . A lower contact angle value (in the presence of SS) indicates that the surface is highly wetted by that liquid.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…DI water showed a contact value of 70° after 8 min. A similar study was reported in the literature where reduction in the contact angle from 62.5° to 48.5° was observed for mulberry leaf extract and 66° to 37° for Henna leaf extract . A lower contact angle value (in the presence of SS) indicates that the surface is highly wetted by that liquid.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, it was established that the natural surfactant was environmentally friendly as well as economical compared to the synthetic surfactant. 22 Rahmati et al 23 introduced natural surfactants from two leaves of mulberry and henna. Surfactants derived from mulberry exhibited IFT reduction from 43.9 to 4.01 mN/m.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they, Zendehboudi et al, (2013), developed thermodynamic modeling for the adsorption of mentioned surfactant onto carbonate rock surface. In addition to these cited works involving the use of biosurfactant, Rahmati et al, (2015), have also investigated experimentally the effect of Natural Leaf-derived Surfactants on Wettability Alteration and interfacial tension reduction in water-oil system for enhanced oil recovery application Ziziphus species (Rhamnaceae) occur in warm-temperate and sub-tropical regions around the world, and they are commonly used as herbs in folk medicine for the treatment of various diseases, such as digestive disorders, weakness, liver complaints, obesity, urinary problems, diabetes, skin infections, fever, diarrhea, and insomnia (Abdel-Zaher et al, 2005). Ziziphus Spina-Christi, for instance, is a wild evergreen tree characterized by spiny branches and small orange fruits that is native to sub-tropical eastern Africa, the Middle East, and the Indian subcontinent, but also widespread in northwestern Africa.…”
Section: Global Availability Of Biosurfactant (Ziziphus Christis) Andmentioning
confidence: 99%
“…Based on the obtained results, the henna extract shows a better performance to reduce the IFT and contact angle of the oil with a sandstone rock. 15 Emadi et al investigated the effects of ZSC and silica nanoparticles on the IFT and RF. The results of IFT measurement show that the ZSC can reduce the IFT, and adding silica nanoparticles to the CMC of ZSC reduces the IFT more.…”
Section: Introductionmentioning
confidence: 99%
“…Rahmati et al compared the effect of the mulberry leaf extract with a natural surfactant named henna on IFT and wettability alteration. Based on the obtained results, the henna extract shows a better performance to reduce the IFT and contact angle of the oil with a sandstone rock . Emadi et al investigated the effects of ZSC and silica nanoparticles on the IFT and RF.…”
Section: Introductionmentioning
confidence: 99%